An Unusual Complication of Pericarditis - Rad, Ashraf; Lange, Ulrich; Makowski, Bartholomaeus; Held, Thomas; Schönwälder, Jürgen; Schmoeckel, Michael (The Thoracic and Cardiovascular Surgeon Reports, 2018)
Background According to current guidelines, acute pericarditis is an inflammatory pericardial syndrome with or without pericardial effusion.Case Description We report on a patient who was treated for purulent pericarditis and developed a fistula from the ascending aorta to the right ventricle (RV), leading to cardiac decompensation. Operative closure of the aortic and RV perforation solved the problem.Conclusion Bacterial pericarditis may lead to life-threatening complications. Early diagnosis and immediate therapy are essential for a successful outcome.
Keywords: pericarditis; complications; fistula; left/right shunt